The Importance of Blood Pressure Control in the Survival of Peritoneal Dialysis Patients Using a Multistate Model - Najafimehr, Hadis; Rahimi Foroushani, Abbas; Yekaninejad, Mir Saeed; Yousefifard, Mahmoud; Hosseini, Mostafa (Kesmas, 2024)
Since less attention has been paid to the effect of passing blood pressure states on the survival of peritoneal dialysis (PD) patients, this study aimed to investigate the survival of PD patients with and without hypertension, estimate the probability of hypertension and determine the influential factors. In this retrospective cohort study, the data of 700 patients visiting dialysis centers from all provinces of Iran from 1997-2009 were analyzed. For data analysis, the multistate survival model was used. The median survival time (months) and five-year survival were 75% and 56%, respectively. Males had a higher probability of hypertension (63%) than females (52%). The risk of death in normotensive patients increased with age and fast blood sugar (FBS) (age: HR = 1.02, p-value <0.001; FBS: HR = 1.03, p-value = 0.034) and decreased with increasing albumin (HR = 0.60, p-value = 0.015). When experiencing hypertension, the death risk increased with age (age: HR = 1.03, p-value<0.001); also, higher serum albumin and blood urea nitrogen (BUN) had a protective effect against mortality (albumin: HR = 0.66, p-value = 0.038; BUN: HR = 0.99, p-value = 0.014). Paying attention to age, obesity, and blood sugar in PD patients seems necessary.